2016
DOI: 10.1093/jmcb/mjw048
|View full text |Cite
|
Sign up to set email alerts
|

SNORD126 promotes HCC and CRC cell growth by activating the PI3K–AKT pathway through FGFR2

Abstract: Small nucleolar RNA (snoRNA) dysfunctions have been associated with cancer development. SNORD126 is an orphan C/D box snoRNA that is encoded within introns 5-6 of its host gene, cyclin B1-interacting protein 1 (CCNB1IP1). The cancer-associated molecular mechanisms triggered by SNORD126 are not fully understood. Here, we demonstrate that SNORD126 is highly expressed in hepatocellular carcinoma (HCC) and colorectal cancer (CRC) patient samples. SNORD126 increased Huh-7 and SW480 cell growth and tumorigenicity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 54 publications
5
81
0
Order By: Relevance
“…Different superscripted lowercase letters indicate significant differences from each other (p < 0.05). EV, empty vector; FABP5, fatty acid binding proteins 5; Met, methionine; NC, negative control; siRNA, small interfering RNA; SE, standard error; SREBP-1c, sterol regulatory element-binding protein 1c [Color figure can be viewed at wileyonlinelibrary.com] show that amino acids, E2, and insulin stimulate SREBP-1c gene expression via PI3K signaling (Fang et al, 2017;X. Huang et al, 2017;Yecies et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Different superscripted lowercase letters indicate significant differences from each other (p < 0.05). EV, empty vector; FABP5, fatty acid binding proteins 5; Met, methionine; NC, negative control; siRNA, small interfering RNA; SE, standard error; SREBP-1c, sterol regulatory element-binding protein 1c [Color figure can be viewed at wileyonlinelibrary.com] show that amino acids, E2, and insulin stimulate SREBP-1c gene expression via PI3K signaling (Fang et al, 2017;X. Huang et al, 2017;Yecies et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SNORD126 is up-regulated in hepatocellular carcinoma and colorectal cancer and upregulates genes involved in the PI3-AKT pathway [68]. Osteoarthritis is the most common degenerative disease of the joints, characterized by joint cartilage breakdown that affects about 4% of the population.…”
Section: Diseases Caused By Snorna Loss Indicate New Functionsmentioning
confidence: 99%
“…Of note, small nucleolar RNAs (snoRNAs), which are non-coding RNAs that are 60-300 nucleotides in length, were proposed to be closely associated with various human diseases, including cancer (11,12). Several studies have reported that certain snoRNAs act as diagnostic or prognostic biomarkers and as therapeutic targets for HCC (13,14). Several in vitro and in vivo studies indicated that certain snoRNAs are involved in the regulation of the genesis and biological behavior of HCC, including cell proliferation, migration, apoptosis, cell cycle and metastasis.…”
Section: Introductionmentioning
confidence: 99%